TECHNOLOGY FOR IMPROVING THE SYSTEM OF PREPARING STUDENTS FOR THE HEALTH PROCESS OF PUBLIC SPORTS (Scientific journal of the Fergana State University, 2024)
In this article, physical culture and recreation and extracurricular activities and mass sports competitions are considered as the most important means and effective mechanism of influence on the preparation of students for the mass sports and recreation process. At the same time, feedback is provided on the tasks of improving the system of preparing students for the process of testing, displaying and evaluating their abilities of such qualities as dexterity, dexterity, strength and patience.